2003
DOI: 10.1063/1.1581380
|View full text |Cite
|
Sign up to set email alerts
|

Exchange-coupling interaction, effective anisotropy and coercivity in nanocomposite permanent materials

Abstract: The inter-grain exchange-coupling interactions, effective anisotropy, and coercivity in nanocomposite Nd2Fe14B/α−Fe magnets were investigated. The effective anisotropy of nanocomposite magnets has been calculated starting from the statistics of boundaries between magnetically hard-hard, hard-soft, and soft-soft grains. The result shows that the effective anisotropy decreases with reduction in grain size and/or increase in soft phase components. When grain sizes reduce to 4–5 nm, Keff decreases to 1/3−1/4 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…Previous calculation has shown that the anisotropy constants K h and K s decrease with the reduction of grain sizes of both hard and soft magnetic phases. 32 The grain with the crystal structure 33 and the site preference of the transition metal ions in the crystal lattice in some cases. 34 The structural defects, such as dislocation or planar defect (twinning) regions introduced by the shock wave, will lead to the local changes in anisotropy constants.…”
Section: Magnetic Properties Of Compactsmentioning
confidence: 99%
“…Previous calculation has shown that the anisotropy constants K h and K s decrease with the reduction of grain sizes of both hard and soft magnetic phases. 32 The grain with the crystal structure 33 and the site preference of the transition metal ions in the crystal lattice in some cases. 34 The structural defects, such as dislocation or planar defect (twinning) regions introduced by the shock wave, will lead to the local changes in anisotropy constants.…”
Section: Magnetic Properties Of Compactsmentioning
confidence: 99%
“…450, 500, 550, 600, 650, and 700°C. it can be seen that the all of composite samples, show a smooth single hysteresis loop, certifying that the two different magnetic phases in the nanocomposites, means hard CoFe 2 O 4 and soft CoFe 2 are exchanged coupled to each other [24]. Indeed soft magnetic moments rotate along with the hard phase due to its external magnetic field and therefore the magnetization and demagnetization of the magnet have a single magnetic phase features.…”
Section: Magnetic Propertiesmentioning
confidence: 80%
“…This value is significantly smaller than the Fe exchange length which exceeds 20 nm [27]. The other physical parameters were exchange constant A = 2 · 10 −11  J/m, magnetic polarization at saturation J s = 2.1 T, and the Gilbert damping constant α = 0.01 [28].…”
Section: Methodsmentioning
confidence: 99%